2019
DOI: 10.4103/ijo.ijo_469_19
|View full text |Cite
|
Sign up to set email alerts
|

Retinal immaturity at first screening and retinopathy of prematurity: Image-based validation of 1202 eyes of premature infants to predict disease progression

Abstract: Purpose: To use the extent of retinal immaturity at the first visit to predict progression to any stage and treatment-requiring retinopathy of prematurity (ROP). Methods: Retrospective, multicenter, nonrandomized, observational, clinical, validation study. In all, 601 Asian Indian preterm infants born < 2000 g and/or < 34 weeks of gestation completing ROP screening with RetCam images taken during each visit were included. A total of 1202 eyes of these infants were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Meanwhile, Jayadev classifies the temporal avascular area of the retina into three degrees: (a) mild: vessels reach posterior zone III; (b) moderate: vessels enter anterior zone II; (c) severe: vessels in posterior zone I or zone II. Thus, type 1 and type 2 ROP are predicted during the first screening visit (27). Jayadev and we have determined that the avascular area of the retina is the main risk factor for ROP requiring treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, Jayadev classifies the temporal avascular area of the retina into three degrees: (a) mild: vessels reach posterior zone III; (b) moderate: vessels enter anterior zone II; (c) severe: vessels in posterior zone I or zone II. Thus, type 1 and type 2 ROP are predicted during the first screening visit (27). Jayadev and we have determined that the avascular area of the retina is the main risk factor for ROP requiring treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Once the optic disc diameter is known, extension of any retinal territory can be quantified in DDs. This measurement unit has been used by several authors to quantify the territory of retinal immaturity (26,27).…”
Section: Eye Examinationmentioning
confidence: 99%
“…However, retinal status is also important for ROP prediction. Previous studies have shown that minor vascular dilation, vascular tortuosity insufficiency in plus disease, the extent of temporal vascularization, and retinal immaturity at the first screening have prognostic significance in the early course of ROP . Thus, our DL system was developed to predict occurrence and severity of ROP using retinal photographs from the first screening along with clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…16,[20][21][22][23][24] However, some of these prediction models are flawed because of they neglect retinal status, which is also important for ROP prediction. [25][26][27] Deep learning (DL) has been recently used for the automated diagnosis of many ocular diseases. [28][29][30][31] Several DL systems have been developed for automated diagnosis of the plus disease of ROP with high accuracy (>89.6%) based on RetCam images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation